Code Mixing Use by Fathia Izzati's YouTube Channel - Yusda, Maharaniguna; Ardi, Havid (Universitas Negeri Padang, 2021)
In bilingual societies, people are able to speak many languages. Commonly, they mix various languages while doing a conversation. This study aims to find out the type of code-mixing used by Fathia Izzati’s YouTube channel. This research used a theory by Hoffman (1991) about three types of code-mixing. This study is descriptive qualitative research. The data were taken from three videos of YouTube Fathia Izzati in 2018 and 2019. The result shows that from 89 data collected, there are two types out of code-mixing that have been found from three types of Hoffman theory. They are Intra-sentential code-mixing (98.88%), involving a change of pronunciation (1.12%), while intra-lexical code-mixing is not found from the data. By the finding, it can be concluded that the types of code-mixing dominantly used by Fathia in her videos is intra-sentential of code-mixing. The speaker’s educational background and parenting patterns greatly influence her speaking style combining the two languages. The reason Fathia speaks like that because she is comfortable and used to mix two languages when speaking. Sometimes there are Indonesian vocabs that are not match for use when speaking, so the speaker is more comfortable mixing with English vocabs and vice versa. Furthermore, the impact of the personal background of a person influenced the speaker to do code-mixing.